Adenomyoepithelioma with a human epidermal growth factor receptor 2-fluorescence in situ hybridization-confirmed ductal carcinoma in situ component: A case report and review of the literature. Issue 42 (16th October 2020) - Amano, Yusuke; Sakaguchi-Tamba, Mio; Sasaki, Yumiko; Oshiro, Hisashi; Fukushima, Noriyoshi; Fujita, Takashi; Masuda, Shinobu; Niki, Toshiro
Abstract: Introduction: Breast adenomyoepithelioma (AME) is a rare tumor composed of myoepithelial cells and ductal or luminal cells. Most cases of AME are benign, but rare cases in which either or both cell types exhibited malignant features have been reported. Due to its rarity, no diagnostic criteria for malignancy have been established for AME. Patient concerns: A 64-year-old woman presented with a mass in her right breast. Fine-needle aspiration cytology and biopsy examinations revealed lesions composed of spindle-shaped cells and round epithelial cells. AME was suspected, and partial mastectomy was performed. Diagnosis: The tumor specimen showed AME, which mainly consisted of spindle-shaped myoepithelial cells with slight atypia, admixed with tubular luminal cells and small areas of atypical intraductal proliferative lesions. No apparent features of malignancy, such as necrosis or invasion, were seen in the myoepithelial cells or the luminal or intraductal component. However, the atypical intraductal component exhibited focal nuclear atypia, a cribriform pattern, and moderate to strong membranous human epidermal growth factor receptor 2 (HER2) immunoreactivity. HER2 amplification was detected in focal regions of the atypical intraductal component by fluorescence in situ hybridization (FISH), which resulted in a diagnosis of AME with ductal carcinoma in situ. Outcomes: The patient did not receive further therapy and was free from tumor recurrence at 23 months after the operation. Conclusion: HER2 FISH might be useful for evaluating suspected AME tumors for malignancy when an atypical ductal lesion that lacks definitive features of malignancy is encountered.